Effi ciency of sex determination by using external morphology of the pelvis in Thai population - Wangdee, Auranat; Thipdet, Wachirapha; Prasitwattanaseree, Sukon; Singsuwan, Phruksachat; Mahakkanukrauh, Pasuk (Biomedical Sciences and Clinical Medicine, 2024)
Objective To study the efficiency of sex determination in a Thai Population by using external morphology of the pelvis. Methods A sample of 300 skeletons from the Forensic Osteology Research Center, Faculty of Medicine, Chiang Mai University were studied. They comprised 150 males and 150 females with an age range from 15 to 96 years. Eleven morphological traits of the pelvis were used for the external morphology as follows: greater sciatic notch, subpubic angle, preauricular sulcus, postauricular sulcus, iliac fossa, acetabulum, ischiopubic ramus ridge, composite arch, ventral arc, pubic bone shape, and dorsal pubic pitting. The score for sex determination by each morphological trait of the pelvis was; 1 = male, 2 = probably male, 3 = sex indeterminate, 4 = probably female, 5 = female. All scores of each morphological trait of the pelvis were analyzed for the accuracy of sex determination. Results The results showed that eleven morphological traits of pelves were present, with a mean accuracy for sex determination of between 72.5% and 98.7%. Subpubic angle, greater sciatic notch, and pubic bone shape were the three most effi cient morphological traits for determining sex, with a mean accuracy of 98.7%, 98.6%, and 98.2%, respectively. Conclusion The most effi cient morphological traits of the pelvis for sex determination were the subpubic angle, greater sciatic notch, and pubic bone shape. These traits should provide an accurate, a rapid and simple determination of sex, which would be benefi cial in the forensic context of Thailand.